Branchial Na+:K+:2Cl− cotransporter 1 and Na+/K+-ATPase α-subunit in a brackish water-type ionocyte of the euryhaline freshwater white-rimmed stingray, Himantura signifer - Ip, Yuen K.; Hiong, Kum C.; Wong, Samuel Z.; Ching, Biyun; Chen, Xiu L.; Soh, Melody M.; Chng, You R.; Ong, Jasmine L.; Wilson, Jonathan M.; Chew, Shit F. (Frontiers in Physiology, 2013)
Himantura signifer is a freshwater stingray which inhabits rivers in Southeast Asia. It can survive in brackish water but not seawater. In brackish water, it becomes partially ureosmotic, but how it maintains its plasma hypoionic to the external medium is enigmatic because of the lack of a rectal gland. Here, we report for the first time the expression of Na+:K+:2Cl− cotransporter 1 (nkcc1) in the gills of freshwater H. signifer, and its moderate up-regulation (~2-fold) in response to brackish water (salinity 20) acclimation. The absence of the Ste20-related proline-alanine-rich kinase and oxidation stress response kinase 1 interaction site from the N-terminus of H. signifer Nkcc1 suggested that it might not be effectively activated by stress kinases in response to salinity changes as in more euryhaline teleosts. The increased activity of Nkcc1 during salt excretion in brackish water would lead to an influx of Na+ into ionocytes, and the maintenance of intracellular Na+ homeostasis would need the cooperation of Na+/K+-ATPase (Nka). We demonstrated for the first time the expression of nkaα1, nkaα2 and nkaα3 in the gills of H. signifer, and the up-regulation of the mRNA expression of nkaα3 and the overall protein abundance of Nkaα in response to acclimation to brackish water. Immunofluorescence microscopy revealed the presence of a sub-type of ionocyte, co-expressing Nkcc1 and Nkaα, near the base of the secondary lamellae in the gills of H. signifer acclimated to brackish water, but this type of ionocyte was absent from the gills of fish kept in fresh water. Hence, there could be a change in the function of the gills of H. signifer from salt absorption to salt excretion during brackish water acclimation in the absence of a functioning rectal gland.